2016
DOI: 10.3171/2015.4.jns159
|View full text |Cite
|
Sign up to set email alerts
|

Cranioplasty after decompressive craniectomy: is there a rationale for an initial artificial bone-substitute implant? A single-center experience after 631 procedures

Abstract: OBJECT The complication rate for cranioplasty after decompressive craniectomy is higher than that after other neurosurgical procedures; aseptic bone resorption is the major long-term problem. Patients frequently need additional operations to remove necrotic bone and replace it with an artificial bone substitute. Initial implantation of a bone substitute may be an option for selected patients who are at risk for bone resorption, but this cohort has not yet been clearly defined. The authors’ goals were to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 26 publications
3
67
3
4
Order By: Relevance
“…Several authors have reported on the risk factors for developing BFR following CP with autologous bone. Schwarz et al28) found that younger than 30 years, the presence of a V-P shunt, and bone flap fragmentation were risk factors for BFR. In addition, Martin et al16) reported that the rate of BFR as 81.8% among 27 patients under 18-years of age who underwent CP with autologous bone after DC, following surgical revision in 54.4 %.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported on the risk factors for developing BFR following CP with autologous bone. Schwarz et al28) found that younger than 30 years, the presence of a V-P shunt, and bone flap fragmentation were risk factors for BFR. In addition, Martin et al16) reported that the rate of BFR as 81.8% among 27 patients under 18-years of age who underwent CP with autologous bone after DC, following surgical revision in 54.4 %.…”
Section: Discussionmentioning
confidence: 99%
“…The choice between autologous bone and alloplastic material for bone reconstruction in cranioplasty remains under debate. 6 Debate also exists concerning techniques for soft tissue recruitment when tissue is lacking over the scalp. 1,7,8 Among techniques, tissue expansion has been demonstrated to be safe when performed over the cranial bone, either before the cranioplasty procedure to increase the rate of success 1,9 or after cranioplasty, away from the implant, to correct sequelar alopecia.…”
Section: Discussionmentioning
confidence: 99%
“…The second one involves implants where allogenic substances are involved such as metals, ceramics or plastics [3]. The patient's own bone is very often resorbed, sometimes causes autoagres sive reaction, and always requires additional operative field [4]. Metals have high thermal conduction and as such in various seasons they easily transmit the heat to or out of the body [5].…”
Section: Methodsmentioning
confidence: 99%